CFD analysis of convective heat transfer from ground mounted solar panels. (August 2016) - Jubayer, Chowdhury Mohammad; Siddiqui, Kamran; Hangan, Horia
Highlights: Investigated wind induced heat transfer from a ground mounted solar panel using CFD. Convective heat transfer coefficients for the PV panel are obtained and analyzed. Correlations are developed between Nusselt and Reynolds numbers. Abstract: The present study deals with the wind induced convective heat transfer from a ground mounted stand-alone solar panel using Reynolds-Averaged Navier–Stokes (RANS) simulation with Shear Stress Transport (SST) k–ω turbulence model. An unsteady solver with a steady inlet condition is employed. The numerical modeling approach is validated for wind flow field around the solar panel with a Particle Image Velocimetry (PIV) experiment performed in the boundary layer wind tunnel. The solar panel is subjected to two different wind directions (0° and 180°), and for each wind direction, three different incoming flows (wind speeds of 1, 5 and 10 m/s at 10 m height) are considered. The Convective Heat Transfer Coefficient (CHTC) distributions on the surfaces of the solar panel are analyzed with respect to the flow field around the solar panel. Similar CHTC distribution is observed on both windward and leeward surfaces of the solar panel where natural convection is dominant over forced convection. In contrast, where forced convection is dominant, higher CHTC values (up-to 128%) are found on the windward surfaces compared to the leeward surfaces of the panel. Relation between the dimensionless CHTC parameter Nusselt number ( Nu ) and the Reynolds number ( Re ) are presented and the results are compared with previous existing correlations. The lowest Re case (1.0 × 10 5 ), which produces the maximum panel surface temperature and thus will result in minimum electrical efficiency of the panel, is identified to be the most critical case in this study.